152 W high-power blue diode laser operated at 447 nm *Project supported by the Beijing Engineering Technology Research Center of All-Solid-State Lasers Advanced Manufacturing and the National High Technology Research and Development Program of China (No. 2014AA032607), the National Natural Science Foundation of China (Nos. 61404135, 61405186, 61308032, 61308033), and the National Key R&D Program of China (Nos. 2016YFB0401804, 2016YFB0402002). (July 2017) - Wu, Peng; Zhang, Ling; Yu, Haijuan; Yuan, Xiandan; Zhang, Zhiyan; Zhao, Pengfei; Zou, Shuzhen; He, Chaojian; Qi, Yaoyao; Yang, Yingying; Li, Gang; Wang, Xubao; et al.
Abstract: We demonstrate a high-power blue diode laser operated at 447 nm combining laser diodes using an optical fiber bundle. As many as 127 diode lasers at 447 nm were coupled into 400 μ m /0.22NA fibers using an aspherical lens group with different focus lengths. The bare fibers were mechanically bundled through high temperature ultraviolet adhesive after the coatings of the 127 fibers were stripped. The diameter of the fiber bundle was 6 mm. The total output power of such a bundle was 152 W with electro-optical conversion efficiency of 27.56% and the RMS power instability was less than ±1% within 3 h.